Habitat selection by Eurasian lynx (Lynx lynx) is primarily driven by avoidance of human activity during day and prey availability during night. Issue 16 (6th July 2017) - Filla, Marc; Premier, Joseph; Magg, Nora; Dupke, Claudia; Khorozyan, Igor; Waltert, Matthias; Bufka, Luděk; Heurich, Marco
Abstract: The greatest threat to the protected Eurasian lynx ( Lynx lynx ) in Central Europe is human‐induced mortality. As the availability of lynx prey often peaks in human‐modified areas, lynx have to balance successful prey hunting with the risk of encounters with humans. We hypothesized that lynx minimize this risk by adjusting habitat choices to the phases of the day and over seasons. We predicted that (1) due to avoidance of human‐dominated areas during daytime, lynx range use is higher at nighttime, that (2) prey availability drives lynx habitat selection at night, whereas high cover, terrain inaccessibility, and distance to human infrastructure drive habitat selection during the day, and that (3) habitat selection also differs between seasons, with altitude being a dominant factor in winter. To test these hypotheses, we analyzed telemetry data (GPS, VHF) of 10 lynx in the Bohemian Forest Ecosystem (Germany, Czech Republic) between 2005 and 2013 using generalized additive mixed models and considering various predictor variables. Night ranges exceeded day ranges by more than 10%. At night, lynx selected open habitats, such as meadows, which are associated with high ungulate abundance. By contrast, during the day, lynx selected habitats offering dense understorey cover and rugged terrain away from human infrastructure. In summer, land‐cover type greatly shaped lynx habitats, whereas in winter, lynx selected lower altitudes. We concluded that open habitats need to be considered for more realistic habitat models and contribute to future management and conservation (habitat suitability, carrying capacity) of Eurasian lynx in Central Europe. Abstract : The distribution of Eurasian lynx ( Lynx lynx ) populations in Central Europe overlaps with human‐dominated landscapes and we expected lynx to modify range use and habitat selection between the phases of the day and over seasons. Lynx used larger areas and selected open habitats at nighttime, while they preferred dense understorey cover and rugged terrain away from human infrastructure during the day with land‐cover type and altitude greatly shaping lynx habitats in summer and winter, respectively. These findings provide new insights into habitat selection by lynx, reveal behavioral adaptations of lynx to human‐modified landscapes and can contribute to improved management and conservation of lynx in Central Europe.